حصر نباتات جوانب الطريق ما بين منطقتي مزدة وقيرة قرب براك - Erteeb, Fathi; اشعيوي فادية جمعة (The Libyan Journal of Science, 2022)
This study concerned with survey and classification of plant species and families that grow in in south of Mizda to the entrance of Sabaha (Gera), along with the concentration of wadis intersections with the road. In this investigation 16 field trips were conducted in order to allow the collection of plant specimens through the season of the year. The field trips lasted more than two years starting 13 of March 2010 to 16 of July 2012. In this study 211 plant species were collected and classified into 156 genera and 39 The Libyan Journa of Science The Libyan Journal of Science- University of Tripoli Vol. 25, No. 01 (2022) 46-70 LJS Vol. 25, No. 01 (2022) 46-70 64 families: Magnoliopsida (dicotyledons) were presented with 35 families, while Liliopsida (monocotyledons) were represented with 4 families. Among these 211 taxa, 9 species were recognized as endemic to Libya, 5 species of which are belonging to the family Asteraceae and 4 species belonging to the family Brassicaceae. The endemic species are Tourneuxia varrifolia Cosson,Perralderia garamantum Cosson, Prolongoa macrocarpa (Cosson & Kralik) Alavi, Tripleurospermum philaenorum (Maire & Weiller) Alavi, Launaea quercifolia (Desf.) Pamp. (Asteraceae), Matthiola glutinosa Jafri., Oudneya africana R.Br., Ammosperma variabile Niger & Le Houerou, Savignya parviflora subsp. parviflora (Brassicaceae). . The investigation indicated that the family Asteraceae with ratio16.11% is the largest in libya followed by Brassicaceae 11.37% then Fabaceae with ratio 10.90% then Poaceae within 10.42%. The Brassicaceae took the place of the Poaceae in present study.